Left Atrial Appendage Thrombus Formation in a Patient on Dabigatran Therapy Associated With ABCB1 and CES-1 Genetic Defect - Gu, Zhi-Chun; Ma, Xiao-Wei; Zheng, Xiao-Yuan; Shen, Long; Shi, Fang-Hong; Li, Hao (Frontiers in Pharmacology, 2018)
Dabigatran, directly targeting thrombin, is widely used for the prevention of stroke in nonvalvular atrial fibrillation (NVAF). We reported a rare case of left atrial appendage thrombus formation in a persistent NVAF patient despite the 31 months uninterrupted treatment with dabigatran 110 mg twice daily. The patient is a carrier of ABCB1 variant alleles with 7 heterozygote single nucleotide polymorphisms (SNPs: rs4148738, rs2235046, rs1128503, rs10276036, rs1202169, rs1202168, rs1202167) as well as CES-1 variant alleles with 2 homozygote SNPs (rs2244613 and rs4122238) and 2 heterozygote SNPs (rs8192935 and rs4580160), which may contribute to the changes of dabigatran plasma concentration. In addition, Drug-drug interaction with atorvastatin may also play a role to decrease dabigatran plasma concentration. There are only four such cases till date, of which had thrombus in the left atrium, reported in the literature. We firstly reported the documented case in a Chinese patient carrying multiple alleles of ABCB1 and CES-1, who suffered from thrombus in the left atrial appendage despite long-term anticoagulation with dabigatran. More clinical data are required to elucidate the impact of CES-1 and ABCB1 polymorphism on dabigatran pharmacokinetics, especially for Asian.